(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the subject of forced deportation of children, as the armed conflicts that occurred in many countries of the world resulted in the resorting of occupied countries and others to the use of this method to achieve military goals, which results in negative effects. For many risks, not limited to their exploitation by others, but the elimination of their identity in not acquiring the language and traditions of their society, which necessitated the existence of international legal protection from these practices, so this study came to demonstrate this protection and its sufficiency, as the Fourth Geneva Convention of 1949 included an explicit prohibition These practices were reinforced through the two protocols of 1977, and these agreements establish general and special protection for children alike.